Inappropriate management conditions, especially for the regressed class, are related to sperm quality in Prochilodus lineatus - De Souza, Thiago G. [UNESP]; Hainfellner, Patrick [UNESP]; Kuradomi, Rafael Y. [UNESP]; Munoz, Mario E. [UNESP]; Honji, Renato M.; Moreira, Renata G.; Batlouni, Sergio R. [UNESP] (Elsevier B.V., 2015)
The aims of this study were to evaluate the characteristics of the reproductive classes and semen quality in curimbata (Prochilodus lineatus) breeders maintained in two different rearing systems. To achieve this goal, cages (Cs) and earthen ponds (EPs) were used as experimental systems to provide unsuitable and suitable conditions, respectively. The fish were maintained under the experimental conditions for 18 months. During this period, males were randomly sampled every 2 months for biometric analysis (n = 30 per sample) and for an evaluation of selected characteristics of the testes (n = 5 per sample). After this period, males maintained in EPs and males maintained in Cs (CMs) were evaluated in induced breeding experiments. We observed that rearing P. lineatus in a C at a high stocking density for the long 18-month period of study produced reductions in growth, testis development, gonadosomatic index values, and sperm quality in the fish. We found differences between the groups in all the reproductive classes examined, especially in the regression class, which showed a pronounced accumulation of immature germ cells in the CMs. In this group, we also noted a less intense transition from a continuous to discontinuous germinal epithelium, with an extended and abnormal but less intense spermatogenic period resulting in decreases in semen volume and sperm concentration in the breeding season. Together, such dysfunctions resulted in the production of low-quality sperm in the CMs, as demonstrated by lower-quality DNA (as evaluated by the comet assay), low fertilization success, and low hatching success. In conclusion, to ensure high-quality semen in P. lineatus, appropriate management conditions must be provided throughout the reproductive cycle, especially for the regressed class, even in winter, two seasons before the breeding season.
Keywords: Spermatogenesis; Sperm quality; Reproductive cycle; Rearing system; Fish farming